2007
DOI: 10.1140/epjst/e2007-00321-6
|View full text |Cite
|
Sign up to set email alerts
|

The SPES direct UCx target

Abstract: SPES (Selective Production of Exotic Species) is an INFN project with the aim to develop a Radioactive Ion Beam (RIB) facility as an intermediate step toward EURISOL. The SPES Project is under realization at the INFN Legnaro National Laboratories site. The SPES Project main goal is to provide a production and accelerator system of exotic beams to perform forefront research in nuclear physics by studying nuclei far from stability. The SPES Project is concentrating on the production of neutron-rich radioactive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The operating temperature should be as high as 2000°C to enable high diffusion rate. Thermomechanical calculations [7] have shown that the SPES target, with its innovative production core, can stand the 8 kW impinging proton beam which produce about 10 13 fissions/s in the target. The short-lifetime neutron-rich exotic isotopes, produced by means of nuclear fission reactions occurring in the disks, must diffuse and eventually effuse to the ionization chamber in the shortest time to avoid their condensation on the cold target regions and their decay before reaching the ionization chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The operating temperature should be as high as 2000°C to enable high diffusion rate. Thermomechanical calculations [7] have shown that the SPES target, with its innovative production core, can stand the 8 kW impinging proton beam which produce about 10 13 fissions/s in the target. The short-lifetime neutron-rich exotic isotopes, produced by means of nuclear fission reactions occurring in the disks, must diffuse and eventually effuse to the ionization chamber in the shortest time to avoid their condensation on the cold target regions and their decay before reaching the ionization chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reactions in inverse kinematics will allow a new class of data to be obtained. The Rear Ion Beam (RIB) will be produced by ISOL technique using the proton-induced fission on a Direct Target of UCx [2]. The proton driver is a Cyclotron with variable energy (30-70 MeV) and a maximum current of 0.750 mA upgradeable to 1.5 mA and split on two exit ports.…”
Section: Facility Descriptionmentioning
confidence: 99%
“…The primary proton beam is delivered by a cyclotron accelerator with energy up to 70 MeV and a beam current of 0.75 mA. Neutron-rich radioactive ions will be produced by uranium fission target 4 per second. The exotic isotopes will be re-accelerated by the ALPI superconducting LINAC 5 at energies of 10 AMeV and higher for masses in the region of A=130 amu, with an expected rate on the secondary target up to 10 9 particles per second.…”
Section: Introductionmentioning
confidence: 99%